A case of limbic encephalitis with initial presentation of chills. Issue 2 (13th May 2019) - Balasundaram, Bharathi; Chen, Zhiyong; Saini, Monica; How Ooi, Chun; Yun Ching Chen, Nicole
Abstract : The Diagnostic and Statistical Manual of Mental Disorders ‐ Fifth Edition (DSM‐5) describes chills (cold) or heat sensations as one of the presenting manifestations of panic attacks. Here the authors describe a case of limbic encephalitis where the presenting feature of chills and piloerection led to an initial incorrect diagnosis of anxiety disorder.